Fluoride Chemistry in Tin Halide Perovskites - Pascual, Jorge; Flatken, Marion; Felix, Roberto; Li, Guixiang; Turren-Cruz, Silver-Hamill; Aldamasy, Mahmoud H.; Hartmann, Claudia; Li, Meng; Di Girolamo, Diego; Nasti, Giuseppe; Husam, Elif; Wilks, Regan G.; et al. (Angewandte Chemie International Edition, 2021)
Tin is the frontrunner for substituting toxic lead in perovskite solar cells. However, tin suffers the detrimental oxidation of SnII to SnIV. Most of reported strategies employ SnF2 in the perovskite precursor solution to prevent SnIV formation. Nevertheless, the working mechanism of this additive remains debated. To further elucidate it, we investigate the fluoride chemistry in tin halide perovskites by complementary analytical tools. NMR analysis of the precursor solution discloses a strong preferential affinity of fluoride anions for SnIV over SnII, selectively complexing it as SnF4. Hard X-ray photoelectron spectroscopy on films shows the lower tendency of SnF4 than SnI4 to get included in the perovskite structure, hence preventing the inclusion of SnIV in the film. Finally, small-angle X-ray scattering reveals the strong influence of fluoride on the colloidal chemistry of precursor dispersions, directly affecting perovskite crystallization.
CRIS-Team Scopus Importer:2021-08-06
Keywords: lead-free systems; perovskite solar cells; tin fluoride; tin halide perovskites; tin oxidation